Electrochemical Impedimetric Platform Based on Con AMIL-101 for Glycoprotein Detection - Li, Qianlan (Langmuir : the ACS journal of surfaces and colloids, 2024)
An electrochemical impedimetric biosensing platform with lectin as a molecular recognition element has been established for the sensitive detection of glycoproteins, a class of important biomarkers in clinical diagnosis. One of the representative metal-organic framework materials, MIL-101(Cr)-NH2, was utilized as the supporting matrix, and its amino groups served as the anchors to immobilize the lectins of concanavalin A (Con A), constituting Con AMIL-101(Cr)-NH2 for the determination of invertase (INV) as a model glycoprotein. The Con A concentration, immobilization time, and incubation time with INV were optimized. Under the optimal conditions, the degree of impedance increase was linearly proportional to the logarithm of INV concentration between 1.0 × 10-16 and 1.0 × 10-11 M, affording a limit of detection as low as 3.98 × 10-18 M. Good specificity, stability, reproducibility, and repeatability were demonstrated for the fabricated biosensing platform. Moreover, real mouse serum samples were spiked with different concentrations of INV. Excellent recoveries were obtained, which demonstrated the biosensing platform's capability of analyzing glycoproteins within a complex matrix